Relationship among anthropometric characteristics, physical fitness, and playing position of ethiopian women the premier league volleyball players - Bekele, B. A. (Bahir dar University, 2023)
In Ethiopia, there is no scientific evidence indicating the anthropometric characteristics and physical fitness level of women premier league volleyball players in relation to their playing positions. Thus, this study was planned to investigate the relationship among anthropometric characteristics, physical fitness, and playing positions of Ethiopian women premier league club volleyball players. By employing a cross-sectional research design the study encompassed 42 women premier league volleyball players. The players were categorized on the bases of playing positions: setters (n=5), middle blockers (n=7), outside hitters (n=11), opposite hitters (n=11), and liberos (n=8). Twenty-three anthropometric and five physical fitness variables were assessed. Descriptive statistics, Pearson Product Moment correlation coefficients (Bivariate), Multiple Regression, and One-Way ANOVA were employed using SPSS (V.26) to evaluate the relationship, prediction, and differences between and among the studied variables. Significant mean differences were separated using TukeyBa,b at P<0.05. The results revealed that Ethiopian women premier league volleyball players had smaller body dimensions and lower physical fitness in muscular strength, explosive power, and agility. But, they were average in muscular endurance and speed. Only some of the anthropometric variables were significantly correlated with the physical fitness components. In the regression model, the anthropometric variables which predict the physical fitness of players were identified. As a result weight and sitting height found to be the most predictor of medicine ball throw and spike vertical jump was predicted by standing reach height and lower leg length. Furthermore, significant differences were observed in standing height, sitting height, standing reach height, arm and leg lengths, and spike and block vertical jumping among players in different playing positions. But, the majority of physical fitness variables were not significantly correlated with anthropometric variables among players in different playing positions. Since position-wise anthropometry and physical fitness are the factors affecting the performance of players in a volleyball game, coaches should consider them during the selection and assignment of players to the proper playing positions.